Tradisi Ubeng Dusun Masyarakat Jawa di Dusun Slatri Kecamatan Kasembon Kabupaten Malang - Auralia F, Rhenna May Diana; Rizki Agung Novariyanto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Slatri Hamlet is a place where the community is all Muslim, because it is a place that is based on the Islamic religion, it cannot be denied that the activities carried out are based on religious activities that contain elements and even the reading of verses from the holy Koran. Ubeng dusun is the core procession in this tradition where residents who take part in ubeng are not allowed to speak at all because they have to read the recommended reading. Previously, Slatri hamlet was a place full of swamps. Because the meaning of the name Slatri itself is rowo sing garing (dry swamp). However, it is not known for certain what the relationship is between the ubeng dusun tradition and the origins of the slatri hamlet which originates from the swamp. However, because of the tradition that has existed for a long time and every year it is carried out precisely in the month of Suro. So until now this tradition has always been carried out because it was ordered by elders and predecessors. This research aims to find out the procession and symbolic meaning of the ubeng village procession carried out by the people of Slatri hamlet. Meanwhile, research data was obtained from interviews with current religious leaders, village heads, and several residents who knew about the ubeng village tradition. So that from the research results obtained, researchers can analyze using descriptive qualitative research methods.